Performan Ayam Broiler yang Diberi Ransum dengan Penggunaan Tepung Limbah Ikan Leubim (Canthidermis maculata) - Zulfan Zulfan; M. A. Yaman; A. Rizki (State Islamic University of Sultan Syarif Kasim Riau, 2020)
The purpose of this study was to determine the performances of broiler chickens fed the diets containing leubim fish (Canthidermis maculata) waste meal. The research was conducted at the Field Laboratory of Animal Husbandry, Faculty of Agriculture, Syiah Kuala University. As many as 80 broiler chicks of MB 202 strain, unsex, produced by PT Japfa, North Sumatra were used in the study. The chicks were fed experimental diets i.e. using leubim fish waste meal with the levels of 0, 4, 8, and 12%, respectively. The research was designed into Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications. Each replication was an experimental unit consisting of 5 chicks. The results of the study indicated that including leubim fish waste meal in the diet was very significantly increased (P<0.01) final body weight, average body weight gain, and feed consumption and decreased feed conversion of broiler chickens compared to the use of commercial local fish meal.